Impact of essential oil and probiotics supplementation on growth performance, serum biomarkers, antioxidants status, bioenergetics and histomorphometry of intestine of Nile tilapia fingerlings challenged with Aeromonas veronii - Walaa S. Raslan; Ahmed Shehab; Aya F. Matter; Hadeer A. Youssuf; Omar Ahmed Farid; Ahmed Sabek; Yasmeen Magdy; Amgad Kadah (BMC Veterinary Research)
Abstract Background Probiotics and essential oils feed supplements are widely used in the aquaculture sector. This study was conducted to evaluate the effects of dietary supplementation with probiotics, essential oils and their combination on growth performance, serum biochemical parameters, antioxidant capacity, resistance against Aeromonas veronii, and intestinal histomorphology of Nile tilapia (Oreochromis niloticus). A total of 360 O. niloticus fingerlings were randomly assigned to four groups (3 replicates/ group; each replicate contains 30 fish) based on the different dietary treatments. The first group was fed a basal control diet (G1), the second group was fed a basal diet supplemented with 0.015% probiotic (Klu-zetar®) (G2), the third group was fed a basal diet with 0.015% essential oil (ACTIVO®) (G3), and the fourth group was fed a basal diet mixed with 0.015% Klu-zetar® and 0.015% ACTIVO®, (G4) for 6 weeks. At the end of the trial fish were intraperitoneally injected with pathogenic bacteria Aeromonas veronii and the fish mortality rate was recorded for 7 days post infection. Results The results revealed that using probiotics and or essential oils in Nile tilapia diets improved growth performance, reduced oxidative stress, enhanced immunity, maintained intestinal integrity, and enhanced resistance to pathogenic infection (P ≤ 0.05). Conclusions It is concluded that the use of probiotics and/ or essential oils enhance the overall outcomes of Nile tilapia, so it is highly recommended to be used in aquaculture management.